Pola Bakteri Ulkus Diabetikum Pada Penderita Diabetes Melitus di RSUD Dr. H. Abdul Moeloek - Haula Rizqiyah; Tri Umiana Soleha; Rizki Hanriko; Ety Apriliana (Majority, 2020)
Diabetes mellitus is a term for heterogeneous of metabolism disturbances for which the main finding is chronic hyperglycaemia. In diabetes mellitus, elevated glycaemic levels increases the risk of microvascular and macrovascular complications. These increase risk of further complications such as peripheral neuropathy which can cause foot ulcerations. Diabetic extremity ulcers develop in approximately 15% of people with diabetes and are a leading cause of hospitalization and amputation among such patient. Diabetic foot ulcer infection followed by amputation contribute dramatically not only to the morbidity among persons with diabetes, but are also associated with severe clinical depression and increased mortality rates. The aim of the study was to determine the bacterial profile of diabetic foot ulcer in RSUD Dr. H. Abdul Moeloek. This study was a descriptive study using a cross sectional study. Sampling was conducted at RSUD Dr. H. Abdul Moeloek and examined in Microbiology-Parasitology Laboratorium in Medicine Faculty of Lampung University. The diabetic foot ulcer swab was taken to identified the bacteria. Bacteria were isolated on nutrient agar, blood agar, Mc Conkey agar, and identified using Gram staining and biochemical test. In the 21 diabetic foot patients, 16 were males (76.2%) and 5 were females (23.8%) and grade-II Wagner’s ulcers were predominant, which is deep ulcer without bony involvement or abscess. In the diabetic foot ulcers cases, 85.7% cases had monomicrobial infections while 14.3% cases had mixed bacterial infection. Gram-positive bacteria accounted for 62.5%. Staphylococcus aureus was the most frequent microorganism yielded (58%). Gram-negative rods accounted for 37.5%. Escherichia coli was the most predominant gram-negative organism (17%). Staphylococcus aureus, Staphylococcus epidermidis, Citrobacter freundii, Escherichia coli, and Proteus mirabilis were found in diabetic foot infections in the present study.